PENGARUH PEMBERIAN EKSTRAK DAUN ANDALIMAN (Zanthoxylum acanthopodium DC.) TERHADAP HISTOLOGIS OVARIUM MENCIT (Mus musculus L.) - Melvariani Syari Batubara; Emita Sabri; Masitta Tanjung (Universitas Medan Area, 2020)
Research the effect of andaliman leaf extract on mice ovaries, volume test material using oral gavage needles as much 0.1 ml / 10 g bb 4 days before and after estrus stage and using RAL non-factorial method consisting of control and treatment group. Treatment consisted of factor test material with dose 2500, 5000, 10000, 20000, 40000 ppm. Chemical content of andaliman leaf extract shown from results study are alkaloids, steroids and saponins. Giving treatment of andaliman leaf extract for 9 days on histological data in the number primary, secondary, De Graff, and atretic follicles experienced fluctuating changes, but statistically did not show a significant difference between treatment and control mice groups, while different results were significantly shown in the number of corpus luteum. Parameters diameter of primary follicles, De Graff, and corpus luteum tended to experience changes that fluctuated, but statistically did not show the difference between the treatment and control mice groups, while the diameter of secondary and atretic follicles showed significantly different results. From the results study, administration of andaliman leaf extract affects histological mice ovaries, because it affects oogenesis and ovulation, but fluctuates, possibly due to crude extract, which has not isolated chemical content.